Vračanje v kapitalizem ali v tržno ekonomijo? - Rus, Veljko (Teorija in praksa, 1997)
Is the way back to capitalism possible at all for postsocialist countries? This is the question the author asks. It is a fact that these countries are experiencing a break through of market regulation which is spreading over the economy field, at the same time reaching the field of social activities. In this way, market relations also have a moral, political and civilisational function. Privatisation occurred contrary to the rules of free market, as privatisation of capital without a market of capital. The political elite should have, at the time, established at least some criteria for justice (equality), which the author suggests and analyses. An analysis on the effectsof privatisation on the social structure follows, concluding with an analysis on workers' stockholding and participation (co-management). The author's thesis is that workers' stockholding does not influence participation.
Keywords: tržno gospodarstvo; soupravljanje; privatizacija; Eastern Europe; Vzhodna Evropa